Conteúdos de matemática do ensino médio nos livros de minicursos da SBHmat (2001-2017) - MENDES, Iran Abreu (Universidade Federal de Mato Grosso, 2022)
Our objective was to characterize the contents of High School Mathematics in short course books classified in the trend in History for the Teaching of Mathematics (HEnM), organized at the Brazilian Center for Reference in Research on the History of Mathematics (CREPHIMat). e epistemological basis for supporting the article is based on a basic conceptual notion established by Mendes (2017, 2020) and Barros and Mendes (2017, 2019). In order to characterize the short course books, we adopted an analysis instrument based on studies related to documentation science. Subsequently, we selected and described the high school mathematics content. e results indicated that the contents covered have didactic potential and can be explored by teachers working in high school, in order to enrich the teaching and learning in mathematics of students at this level of education.